Copper and Zinc doped ZrO2 Nanoparticles as High-Performance Catalysts for Efficient Removal of Rose Bengal Dye under Solar Light Irradiation - Arumugam Muthupandiyammal; Alagar Subalakshmi; Balasubramani Kavitha (Journal of Water and Environmental Nanotechnology)
In this study, new solar light-sensitive photocatalysts on Cu, Zn-ZrO2 for the treatment of organic dyes in wastewater were investigated. Pure and doped ZrO2 photocatalysts were synthesized by co-precipitation techniques. The nanoparticles were analyzed by UV-Vis-DRS, FTIR, XRD, and SEM-EDX techniques. The XRD results of the pure ZrO2 confirmed the formation of a single-phase tetragonal structure. SEM images depict the uniform flakes with plated-like structures for Cu, Zn-ZrO2, and ZrO2 nanoparticles. Optical properties were studied using a UV–Vis spectrometer and obtained band gap range between 4.1 eV and 2.1 eV. The optimized doped sample achieved 98% degradation of RB within 120 mins of solar light irradiation. Cu/Zn-ZrO2 (98%) shows higher photocatalytic activity than Cu/ZrO2 (87%), Zn/ZrO2 (70%) and ZrO2 (50%). The superior photocatalytic activity of optimally doped samples under solar light is credited to suitable doping content, crystalline size, suitable bandgap, and the ability to decrease the charge carrier’s recombination rate.